(untitled) (Eurasian Journal of Engineering and Technology, 2022)
The efficiency of the vehicle’s traffic composition is significantly affected by the cost and timeliness of transporting people and goods. There are a lot of these engines in terms of internal combustion type (ICE) and the characteristics depend on the fact that most of them are diesel. In addition, more than 90% of trucks and more than 60% of large buses are equipped with diesel engines. The share of passenger cars with diesel engines is also constantly increasing accordingly. The work activities improve and the most strict Euro6 ecological requirements answer given for diesel engines electron fuel supply systems with equipped